2020
DOI: 10.1093/jmcb/mjaa038
|View full text |Cite
|
Sign up to set email alerts
|

MDMX phosphorylation-dependent p53 downregulation contributes to an immunosuppressive tumor microenvironment

Abstract: A role of tumor suppressive activity of p53 in the tumor microenvironment (TME) has been implicated but remains fairly understudied. To address this knowledge gap, we leveraged our MdmxS314A mice as recipients to investigate how implanted tumor cells incapacitate host p53 creating a conducive TME for tumor progression. We found that tumor cell-associated stress induced p53 downregulation in peritumor cells via a MDMX-Ser314 phosphorylation-dependent manner. As a result, an immunosuppressive TME was developed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Maintaining P53 levels in TME is related not only to a significant increase in macrophage infiltration into tumors but also to M1 polarization. The reduction of P53 effectively reversed the immunosuppressive status of TME (36). Although AQP9mediated chemoresistance of human melanoma downregulated the expression of apoptosis genes P53 and Bax (37), which is consistent with our study, AQP9 is positively correlated with the increase in M2 polarization and may exert its tumor suppressor effect through the P53 pathway according to our results.…”
Section: Discussionsupporting
confidence: 91%
“…Maintaining P53 levels in TME is related not only to a significant increase in macrophage infiltration into tumors but also to M1 polarization. The reduction of P53 effectively reversed the immunosuppressive status of TME (36). Although AQP9mediated chemoresistance of human melanoma downregulated the expression of apoptosis genes P53 and Bax (37), which is consistent with our study, AQP9 is positively correlated with the increase in M2 polarization and may exert its tumor suppressor effect through the P53 pathway according to our results.…”
Section: Discussionsupporting
confidence: 91%
“…MDMX, however, can translocate into the nucleus upon binding to and forming a complex with MDM2. Given its cytoplasmic distribution, it is conceivable that MDMX serves as the sentinel for various signaling cues directed towards the MDM2/MDMX complex and aimed at either suppressing or activating p53 ( Shadfan et al, 2012 ; Wang et al, 2020 ). Studies have shown that in response to growth-promoting signals, many mitogenic protein kinases can inhibit p53 activation via enhancing MDM2/MDMX stability and, specifically, through post-translational modifications of MDMX ( Lopez-Pajares et al, 2008 ; Gerarduzzi et al, 2016 ).…”
Section: The Regulation Of P53mentioning
confidence: 99%
“…However, how p53 participates in regulating the tumor immune microenvironment is only beginning to be investigated. A recent study by Wang et al showed that implanted mammary carcinoma cells acted on their surroundings in the host to induce an immunosuppressive microenvironment facilitating tumor growth ( Wang et al, 2020 ). A contribution of p53 to the regulation of the immune microenvironment was demonstrated with a genetically engineered mouse model expressing a phospho-resistant MDMX.…”
Section: P53-mediate Homeostatic Regulation Of Immune and Inflammatory Responsementioning
confidence: 99%
“…TP53 mutational status may also be critical within the microenvironment itself. In p53 null mice, the size of tumor xenografts are greatly increased and correlate with the presence of myeloid derived suppressor cells, regulatory T cells, and a loss of effector function [ 100 , 101 ]. CD47 blockade may therefore be able to exploit how TP53 mutations reshape the local innate and adaptive immune response.…”
Section: Targeting Cd47 In Acute Myeloid Leukemiamentioning
confidence: 99%